2020
DOI: 10.3389/fnins.2020.00670
|View full text |Cite
|
Sign up to set email alerts
|

Down Syndrome Is a Metabolic Disease: Altered Insulin Signaling Mediates Peripheral and Brain Dysfunctions

Abstract: Down syndrome (DS) is the most frequent chromosomal abnormality that causes intellectual disability, resulting from the presence of an extra complete or segment of chromosome 21 (HSA21). In addition, trisomy of HSA21 contributes to altered energy metabolism that appears to be a strong determinant in the development of pathological phenotypes associated with DS. Alterations include, among others, mitochondrial defects, increased oxidative stress levels, impaired glucose, and lipid metabolism, finally resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 197 publications
(312 reference statements)
1
53
0
2
Order By: Relevance
“…In addition, studies from Potier’s laboratory and others reported endosomal enlargement in peripheral and neuronal cells from DS cases supporting a role for early endosomal dysfunction and aberrantly regulated endosomal trafficking in the toxic events leading to DS pathology in the brain and in other organs [ 48 , 49 , 50 , 51 , 52 ]. An increasing number of studies also demonstrated that DS subjects are at high risk to develop either peripheral or brain metabolic defects, characterized by the dysregulation of the insulin signaling with reduced downstream pathways, and altered mitochondrial structure and function that, in turn, is associated with increased ROS production and OS [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies from Potier’s laboratory and others reported endosomal enlargement in peripheral and neuronal cells from DS cases supporting a role for early endosomal dysfunction and aberrantly regulated endosomal trafficking in the toxic events leading to DS pathology in the brain and in other organs [ 48 , 49 , 50 , 51 , 52 ]. An increasing number of studies also demonstrated that DS subjects are at high risk to develop either peripheral or brain metabolic defects, characterized by the dysregulation of the insulin signaling with reduced downstream pathways, and altered mitochondrial structure and function that, in turn, is associated with increased ROS production and OS [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lipidomic and clinical chemistry analysis of plasma showed that Dp1Tyb mice have characteristics of a pre-diabetic state with hepatic steatosis, conditions that are seen in people with DS 65 . Further work is needed to determine if the animals could be induced to develop glucose intolerance, for example by being fed a high-fat diet.…”
mentioning
confidence: 99%
“…Given the obesity comorbidity in DS, we studied how the microbiome profile of Ts65Dn changed upon high-fat diet feeding. In standard chow conditions, Ts65Dn are in fact leaner than their wild type littermates (Fructuoso et al, 2018;Dierssen et al 2020), and we found A. muciniphila overrepresentation in Ts65Dn, which is associated with lowering body fat mass (Everard et al 2013) and improving glucose homeostasis (Shin et al 2014). Interestingly, upon access to a high-fat diet Ts65Dn mice present increased body adiposity and gain more weight than WT (Fructuoso et al 2018).…”
Section: Discussionmentioning
confidence: 67%
“…DS has an incidence of 1 in 1000 births and affects more than 5 million people worldwide (World Health Organisation report) and causes numerous developmental anomalies such as intellectual disability, facial dysmorphology, congenital defect of heart and gut, immunodeficiencies (Dierssen, 2012). With development of medicine and social care the lifespan of persons with DS is significantly prolonged in the past decades (Zigman, 2013), however, this prolongation comes together with a parallel increase of risk for age-related diseases, such as Alzheimer's disease, increased rate of infections, hypertension and obesity (Nakamura and Tanaka, 1998;Dierssen et al 2020). Some of the DS comorbidities, such as functional bowel disease (Gevers et al 2014), obesity (Castaner et al 2018), reflux oesophagitis (Cho and Blaser, 2016) or Alzheimer disease (Minter et al, 2016) were recently found to be related to certain microbiome features, it became highly interesting to characterize the DS microbiome.…”
Section: Introductionmentioning
confidence: 99%